Assessing Physical Activity Levels in Filipino Americans With Hypertension Using the Rapid Assessment of Physical Activity Questionnaire. (May 2017) - Angosta, Alona D.; Serafica, Reimund
Regular physical activity decreases the risk of cardiovascular disease and premature death. Little research has been conducted among Filipino Americans about their level of physical activity. Using the validated Rapid Assessment of Physical Activity questionnaire, we examined the activity level of Filipino Americans ( N = 108) from the southwest region of the United States and compared the findings with national physical activity guidelines. The sample mean age was 65 years, 98% were born in the Philippines, 31% had some college education, 71% were married, and 40% had incomes less than $25, 000. The mean blood pressure was 140/85 mmHg. The mean score for physical activity level was 5 (max. score 7) and for strength and flexibility 1 (max. score 3), which is less than the recommended guidelines. Lifestyle strategies to increase physical activity and reduce obesity and hypertension in this high-risk, understudied population are warranted.